If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+2=4(x+1)
We move all terms to the left:
3(x+2-(4(x+1))=0
| (x+7)^2-36=0 | | 48/2=z | | 5x-2x+1=3x+15x-2/4 | | 1v+3=17 | | 56-11x+4x=77 | | -1=5x-16 | | x^2+20x+28=0 | | 4*x+7=36 | | y-2=22 | | 3n-5=7n-21 | | X^2/(.25-2x)^2=2 | | 2/5+1/10=1/2(n+4) | | 2n-5=9n+37 | | T^2+28t+625T=0 | | -(x-1)(-2)=3 | | (x+10)^2-72=0 | | -3a+56+5(28)+85+180=0 | | (x/4)-(5/2)=(x/8) | | 12/1.12=3/e | | X+6=-1+2x | | 3/2x+1/4=13/4 | | 0.5x-3.5=0.2×-0.5 | | 5x=10^12 | | 5/8=25/c | | x-3=8(x-3) | | x+0.1=4.9 | | x+6-8x=6 | | M+20=9m-4 | | n+1.3=-1.2 | | 4(-2-6x)=184 | | 1.12/12=e/3 | | 490=4.9t^2 |